Groundwater‐Controlled Deposition of Equatorial Layered Deposits in Central Arabia Terra, Mars. Issue 3 (20th March 2023) - Di Pietro, I.; Schmidt, G.; Tangari, A. C.; Salese, F.; Silvestro, S.; Fairén, A. G.; Marinangeli, L.; Pondrelli, M.
Abstract: Equatorial Layered Deposits (ELDs) reveal aspects of past depositional environments useful for timing climatic and geological events on Mars. However, their formation has several contending hypotheses which reflect a diverse range of possible environments. To better constrain their formation mechanism, we analyzed the stratigraphic and mineralogical characteristics and mapped the distribution of ELDs within three close craters, Sera, Jiji, and an unnamed crater in central Arabia Terra. Analyses of craters' geology allowed us to reconstruct the paleo‐environments where ELDs have been deposited. Thinning and thickening sequence trends show shared and repeated variations in the depositional environment, reflecting sediment accumulation strongly controlled by a regional groundwater reservoir. Layered deposits are characterized by monohydrated and polyhydrated sulfate signatures implying an interaction between water and rock in acidic conditions. Our study contributes to the understanding of regional geological processes in Arabia Terra revealing long‐term aqueous activity. Plain Language Summary: Despite years of orbital observations of the surface of Mars, mid‐to low‐latitude layered deposits (LD) in Arabia Terra are not yet fully understood. These deposits record an important geological sequence of the early Martian history, but their exact formation, specifically the putative role of the water in their formation and preservation, remains an unanswered question. This study helps in further understanding these processes by comparing and contrasting LD present in craters in very close proximity to each other. In this way, proposed hypotheses benefit from having a control that is not limited to a singular crater or location. Our study contributes to the understanding of regional geological processes in Arabia Terra revealing long‐term aqueous activity. Results combine various analyses, including measurements of layer thickness and attitudes, orbital spectroscopy, basin geometry, and morphologies aimed at reconstructing the geological evolution of the area. In particular, we interpreted that LD were emplaced in a depositional environment reflecting sediment accumulation strongly controlled by a regional groundwater reservoir in acidic conditions. Key Points: Regional groundwater fluctuations influenced the deposition, mineralogy, and preservation of Equatorial Layered Deposits (ELDs) in Arabia Terra Four different stratigraphic sequences of layered deposits have been identified on the basis of strata thickness and attitude Mineralogical analyses of ELDs suggest the presence of different levels of hydration of sulfates